1988
DOI: 10.1111/j.1365-2621.1988.tb00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chilling injury in ripe Alphonso mango fruit in cold storage by temperature conditioning

Abstract: The influence of ripening temperature and cold conditioning of pre-climacteric fruits on the incidence of chilling injury (CI) in ripe mango fruits cv. Alphonso during refrigerated storage was investigated. Fruits previously held and ripened at tropical ambient temperature (AT, 27-34°C) developed CI (skin staining or browning) when ripe fruits wcre subsequently stored at 5 , 10, or 15°C for shelf-life extension. Fruits held and ripened at 20"C+loC, RH 85-90% showed little evidence of CI when subsequently store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…The changes in carotenoid levels during cold storage have not been studied much, but similar results have been observed in two cultivars of yellow nectarines, 25 in carrots, 38 or in mangoes. 39 With regard to evolution of carotenoids during shelf life, increases of β-carotene and β-cryptoxanthin in peaches held in air at 20 °C for 8 days after harvest were already observed by Caprioli et al 26 Similar results have also been described previously for kiwifruit stored for 2 months at 0 °C and maintained for 7 days at 25 °C. 36 As shown in Table 3, total polyphenol content ranged from 8.6 to 10.4 mg/100 g. Hydroxycinnamic acids, accounting for 75−82% of the total polyphenol content, were found to be predominant, followed by anthocyanins (8−16%), flavanols (4−7%), and flavonols (4−5%).…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…The changes in carotenoid levels during cold storage have not been studied much, but similar results have been observed in two cultivars of yellow nectarines, 25 in carrots, 38 or in mangoes. 39 With regard to evolution of carotenoids during shelf life, increases of β-carotene and β-cryptoxanthin in peaches held in air at 20 °C for 8 days after harvest were already observed by Caprioli et al 26 Similar results have also been described previously for kiwifruit stored for 2 months at 0 °C and maintained for 7 days at 25 °C. 36 As shown in Table 3, total polyphenol content ranged from 8.6 to 10.4 mg/100 g. Hydroxycinnamic acids, accounting for 75−82% of the total polyphenol content, were found to be predominant, followed by anthocyanins (8−16%), flavanols (4−7%), and flavonols (4−5%).…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…Although the exact critical temperature for the induction of chilling injury was not determined, our results suggest that it might be as high as 15°C. In a recent study Thomas & Joshi (1988) reported that, unlike many other tropical and subtropical fruits such as avocado, banana and papaya, ripe Alphonso mangoes are more sensitive to chilling injury than pre-climacteric fruit; our results indicate that ripe wild mangoes are similar, and that refrigerated storage is not a viable option. However, Thomas & Joshi (1988) also found that ripening Alphonso mangoes at 20°C avoided chilling injury, although with some loss of quality, and that variety and growth conditions can influence sensitivity of ripe mangoes to chilling.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, delaying fruit ripening also reduces fruit susceptibility to postharvest pathogens and, therefore, many previous research studies have focused on delaying the rate of fruit ripening. A range Horticulturae 2019, 5, 1 2 of 12 of physical and chemical methods have been successfully employed to delay ripening and senescence, and include controlled atmosphere storage [4], low and high temperature treatments [5,6] and simple chemical treatments including carbonate and bicarbonate solutions [7].…”
Section: Introductionmentioning
confidence: 99%